The Politics of Protection: Body Image, Social Pressures, and the Misrepresentation of Young Black Women - Poran, Maya A. (Sex Roles : A Journal of Research, 2006)
As part of a larger multi-method study, 15 Black women college students participated in focus group discussions on the body. Contrary to popular theories that propose that Black women are protected by a “Black Culture” that buffers them from negative effects of body representations—thereby leaving them with higher body esteem—the themes that emerged in the focus group discussions indicate that young Black women are indeed feeling (1) pressures to be thin, (2) pressures from the preferences of men of diverse ethnicities, (3) competition with other Black women in the realms of beauty, and (4) a strong sense of being misrepresented by media images of thin Black women. These results not only indicate that body image issues are of real pressing concern to young Black women, but that psychological research methodologies may be adding to the misrepresentation of young Black women and their struggles. Qualitative methods must be utilized in order to hear more clearly the voices of Women of Color.
Keywords: 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; image corporelle; intersectionnalité; new york; premier cycle; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; états-unis

Domestic violence at the intersections of race, class, and gender: challenges and contributions to understanding violence against marginalized women in diverse communities - Sokoloff, Natalie J; Dupont, Ida (Violence against women, 2005)
This article provides a comprehensive review of the emerging domestic violence literature using a race, class, gender, sexual orientation intersectional analysis and structural framework fostered by women of color and their allies to understand the experiences and contexts of domestic violence for marginalized women in U.S. society. The first half of the article lays out a series of challenges that an intersectional analysis grounded in a structural framework provides for understanding the role of culture in domestic violence. The second half of the article points to major contributions of such an approach to feminist methods and practices in working with battered women on the margins of society.
Keywords: 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; care; corps; cours; criminologie; discipline; féminisme afroaméricain; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; sociologie; thématiques; violences; états-unis